Sound propagation and quantum-limited damping in a two-dimensional fermi gas - Bohlen, Markus; Sobirey, Lennart; Luick, Niclas; Biss, Hauke; Enss, Tilman; Lompe, Thomas; Moritz, Henning (Physical review letters, 2020)
Strongly interacting two-dimensional Fermi systems are one of the great remaining challenges in manybody physics due to the interplay of strong local correlations and enhanced long-range fluctuations. Here, we probe the thermodynamic and transport properties of a 2D Fermi gas across the BEC-BCS crossover by studying the propagation and damping of sound modes. We excite particle currents by imprinting a phase step onto homogeneous Fermi gases trapped in a box potential and extract the speed of sound from the frequency of the resulting density oscillations. We measure the speed of sound across the BEC-BCS crossover and compare the resulting dynamic measurement of the equation of state both to a static measurement based on recording density profiles and to quantum Monte Carlo calculations and find reasonable agreement between all three. We also measure the damping of the sound mode, which is determined by the shear and bulk viscosities as well as the thermal conductivity of the gas. We find that the damping is minimal in the strongly interacting regime and the diffusivity approaches the universal quantum bound (h) over bar /m of a perfect fluid.
Gesehen am 16.07.2020